Photoionization cross section in a spherical quantum dot: Effects of some parabolic confining electric potentials - Tshipa, M. (Condensed Matter Physics, 2017)
A theoretical investigation of the effects of spatial variation of confining electric potential on photoionization
cross section (PCS) in a spherical quantum dot is presented. The potential profiles considered here are the
shifted parabolic potential and the inverse lateral shifted parabolic potential compared with the well-studied
parabolic potential. The primary findings are that parabolic potential and the inverse lateral shifted parabolic
potential blue shift the peaks of the PCS while the shifted parabolic potential causes a red shift. Представлено теоретичне дослiдження впливу просторової змiни обмежуючих електричних потенцiалiв
на перерiз фотоiонiзацiї в сферичнiй квантовiй точцi. Розглянутi тут профiлi потенцiалiв є змiщений параболiчний потенцiал i дзеркальне зображення змiщеного параболiчного потенцiалу, якi порiвнюються
з добре вивченим параболiчним потенцiалом. Основний результат — це те, що параболiчний потенцiал i дзеркальне зображення змiщеного параболiчного потенцiалу зсувають пiки перерiзу фотоiонiзацiї у
фiолетовий дiапазон, тодi як змiщений параболiчний потенцiал спричинює червоний зсув.